Maintenance or change? Examining the reinforcing spiral between social media news use and populist attitudes. Issue 13 (3rd October 2022) - Schumann, Sandy; Thomas, Fabian; Ehrke, Franziska; Bertlich, Tisa; Dupont, Julia C.
ABSTRACT: Citizens around the world increasingly express support for populism. Here, we apply the reinforcing spirals model to examine whether, and how, social media news use shapes populist attitudes over time. Specifically, we assess if using social media as a news source serves to maintain existing populist attitudes or facilitates a shift in attitudes to a more extreme position. A cross-sectional survey ( N 1 = 195) highlighted a positive correlation between social media news use and populist attitudes. A four-wave longitudinal survey ( N 2 = 386) further showed that this relationship reflects media and selection effects. Over a period of three months, more frequent social media news use predicted stronger populist attitudes at subsequent measuring points. In addition, higher levels of populist attitudes were related to more frequent social media news consumption in the following waves. However, the frequency of social media news use did not change over time and populist attitudes did not become stronger during the study period. Taken together, the findings indicate that social media news use contributed to the maintenance of populist attitudes at a stable level. There is no evidence to suggest social media news use predicted more extreme populist attitudes. We discuss these results with respect to the (potentially continued) rise of populism; we also critically reflect on the phenomenon of attitude polarization online.